Calm ocean, stormy sea: atmospheric and oceanographic observations of the Atlantic during the Atlantic References and Convection (ARC) ship campaign - L. Köhler; L. Köhler; J. Windmiller; D. Baranowski; M. Brennek; M. Ciuryło; L. Hayo; D. Kȩpski; S. Kinne; B. Latos; B. Lobo; T. Marke; et al. (Earth System Science Data)
During the Atlantic References and Convection (ARC) ship campaign with the reference MSM114/2, which took place in early 2023, the German research vessel Maria S. Merian travelled from Mindelo, Cape Verde, to Punta Arenas, Chile. One of the main objectives of ARC was to obtain vertically resolved cross sections of the Intertropical Convergence Zone (ITCZ). To this end, we crossed the ITCZ three times in the meridional direction. We present the atmospheric and oceanographic measurements collected during ARC in a standardised way to facilitate working with data from different instruments and to make the data easily accessible. This approach is not limited to ARC but could serve as a prototype for future (and past) ship campaigns. We present data from the integrated ship sensors (DSHIP); a humidity and temperature profiler (HATPRO); a ceilometer; aerosol instruments (DustTrak, Microtops, and Calitoo); radiosondes; uncrewed aircraft vehicles (UAVs); and conductivity, temperature, and depth (CTD) profiles of the upper ocean. We distinguish between temporal continuous data (DSHIP, HATPRO, Ceilometer, and DustTrak) from point measurements (radiosondes, UAVs, CTDs, Calitoo, and Microtops). To illustrate the data sets provided, we present examples of measurements taken during the three crossings of the ITCZ and during a storm in the Roaring Forties in the South Atlantic at the end of the campaign. An overview of all available data sets, including DOIs and download links, can be found in Köhler et al. (2024a) with the DOI https://doi.org/10.1594/PANGAEA.966616. For references to the individual data sets, please refer to the “Data availability” section.